Spartacus : an international magazine for gay men. (Amsterdam : Spartacus, 1980)
Fonds Suzan Daniel (FSD)
Periodiciteit : onregelmatig
Redactie : PO Box 3496, 1001 AG Amsterdam
Vanaf (1981) 2 : an international magazine for and about gay men
Engels
Periodiek